Neuro-ophthalmic complications of immune checkpoint inhibitor therapy: Current status and future directions - Winges, Kimberly M.; Gordon, Lynn K. (Frontiers in Ophthalmology, 2022)
Since 2011, use of immune checkpoint inhibitors (ICI) in cancer immunotherapy dramatically expanded, both alone and in combination with either a different cancer treatment or with two different ICIs. With this increase in use have come a myriad of adverse effects from enhanced immune activation, including ophthalmic and neurologic immune related adverse events (irAE). Neuro-ophthalmic immune related adverse events (NOirAE) associated with use of ICIs are increasingly recognized and their severity may actually limit use of potentially life-saving immunotherapy. NOirAEs comprise a wide variety of presentations involving both the central and peripheral nervous system. They cause afferent or efferent visual dysfunction, including among them optic neuropathy and edema, orbital inflammatory disease, and ocular myasthenia. While treatment for irAEs typically involves immunosuppression with corticosteroids, there is no expert consensus regarding best practices for treatment of NOirAEs and whether to stop ICI immunotherapy for the cancer or not. This state-of-the-art review explores the pathophysiologic basis for NOirAEs, provides a framework for categorizing them within neuro-ophthalmology, and discusses what is needed to close the current knowledge gaps in diagnosis and management of an increasing population of cancer patients requiring neuro-ophthalmic care.